2009
DOI: 10.1210/en.2008-1250
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptor 39 Deficiency Is Associated with Pancreatic Islet Dysfunction

Abstract: G protein-coupled receptor (GPR)-39 is a seven-transmembrane receptor expressed mainly in endocrine and metabolic tissues that acts as a Zn(++) sensor signaling mainly through the G(q) and G(12/13) pathways. The expression of GPR39 is regulated by hepatocyte nuclear factor (HNF)-1alpha and HNF-4alpha, and in the present study, we addressed the importance of GPR39 for glucose homeostasis and pancreatic islets function. The expression and localization of GPR39 were characterized in the endocrine pancreas and pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 44 publications
5
81
2
1
Order By: Relevance
“…Interestingly, although not coexpressed with insulin-producing b-cells in the pancreas, Ob secretion has been shown in human pancreatic islet cells and in the INS-1E b-cell line, suggesting that, similarly to ghrelin, Ob may act in the pancreas through autocrine/paracrine mechanisms (Granata et al 2008). Besides GPR39 potentially being the receptor of Ob (Zhang et al 2005, Dong et al 2009, its expression has been demonstrated both in human and rodent endocrine pancreas and in b-cell lines (Holst et al 2009, Tremblay et al 2009), raising the possibility of GPR39 ligands directly influencing pancreatic islet activity.…”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, although not coexpressed with insulin-producing b-cells in the pancreas, Ob secretion has been shown in human pancreatic islet cells and in the INS-1E b-cell line, suggesting that, similarly to ghrelin, Ob may act in the pancreas through autocrine/paracrine mechanisms (Granata et al 2008). Besides GPR39 potentially being the receptor of Ob (Zhang et al 2005, Dong et al 2009, its expression has been demonstrated both in human and rodent endocrine pancreas and in b-cell lines (Holst et al 2009, Tremblay et al 2009), raising the possibility of GPR39 ligands directly influencing pancreatic islet activity.…”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 99%
“…Interestingly, isolated, perfused islets from GPR39 null mice have recently been shown to secrete less insulin in response to glucose stimulation than islets from wild-type littermates (Holst et al 2009). Moreover, GPR39 null mice fed with either a low-fat/ high-sucrose or high-fat/high-sucrose diet show decreased serum insulin levels during an oral glucose tolerance test in the face of unchanged insulin tolerance (Tremblay et al 2009), suggesting that GPR39 is required for insulin secretion and may be a potential target for the treatment of diabetes.…”
Section: Effect Of Ag Uag and Ob On Insulin Secretion In Pancreaticmentioning
confidence: 99%
“…GPR39 has been reported to be associated with type 2 diabetes (Holst et al, 2009;Verhulst et al, 2011) and depression (Młyniec and Nowak, 2015;Młyniec et al, 2015a,b,c). GPR39 has been found to be expressed in mouse intestinal fibroblastlike cells (Zeng et al, 2012), human colon adenocarcinoma HT-29 cells (Yasuda et al, 2007;Cohen et al, 2012Cohen et al, , 2014, rat colon BRIN-BD11 cells (Moran et al, 2016), and mouse pancreatic epithelial NIT-1 cells (Fjellström et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Intercellular Zn communication mediated through the Zn-sensing receptor GPR39 is also involved in regulating epithelial cell repair (Sharir et al 2010) and endocrine pancreatic function (Holst et al 2009). Also supporting the role of Zn as a neurotransmitter, Hosie et al identified two Zn-binding sites and characterized a third in the GABA receptor using site-directed mutagenesis (Hosie et al 2003).…”
Section: Zn Acts As a Neurotransmittermentioning
confidence: 99%